Exchange Rate, Inflation, Interest Rate and Economic Growth: How They Interact in ASEAN - suciany, Amanda Dwi; Rut Damayanti, Cacik; Darmawan, Ari (FIA UB, 2024)
This research investigates the interplay between exchange rates, inflation, and interest rates, collectively influencing economic growth in the ASEAN Region. The study constructs a comprehensive analytical framework based on economic theories like purchasing power parity, monetary theories of inflation, and the International Fisher Effect theory of interest. It aims to discern the individual and interactive effects of exchange rate movements, inflation, and interest rate fluctuations on overall economic output. Through empirical analysis covering 2007 to 2022 in Southeast Asia, using a saturated sample, the study employs statistical models and time-series analysis. Classical assumption tests, descriptive statistics, and path analysis unravel the nuanced influence of these macroeconomic factors on GDP variations. Findings indicate that exchange rates have a positive yet statistically insignificant impact on inflation while significantly and positively influencing interest rates. Inflation, in turn, significantly affects interest rates. Exchange rates negatively impact gross domestic product, supporting the idea that a competitive real exchange rate fosters growth in developing regions. Additionally, inflation and interest rates negatively impact economic growth in the ASEAN Region, confirming the research hypotheses. This study provides significant insights into the intricate interactions shaping economic dynamics in Southeast Asia.